THE IDENTIFICATION OF VITALITY FACTORS FOR PUBLIC OPEN SPACE AT THE CISADANE RIVER AREA, TANGERANG CITY - Freddy, Yos; A. Hadi Prabowo (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2021)
The Cisadane Riverside area is currently under the attention of Tangerang City Government as an object of restructuring the part of Tangerang old city, by providing public spaces, with the hope that the area can be revitalized.The level of success in revitalizing the area needs to be identified, so that it is useful for the next structuring activity in anticipation of the quietness of the area. This study aims to pinpoint perceptions and factors that influence the vitality of public space at Cisadane riverbank area, Tangerang City. Data were gathered by conducting direct observation and distributing questionnaires by means of Google Form, and rating the perception through the Likert scale. The number of respondents was 116, comprising of 18 people aged 15-30 years, 86 people 31-50 years and 12 people over 50 years old. The variables studied involve comfort, security, safety and pleasure, in relation to the vitality of the Cisadane Riverbank area. The results reveal that there are four factors stimulate the vitality of Cisadane riverside area, namely the physical condition of parking lot, the availability of parking space, the operational hours of trading activities and the condition of fire protection (public hydrants and evacuation routes). Keywords : Vitality, Public Spaces, Riverbank Area